Mitigasi Bencana Banjir Genangan pada Blok Drainase Lhok Banie Kota Langsa Melalui Pemodelan Profil Muka Air dan Kolam Retensi - Nina Shaskia; Azmeri Azmeri; Ziana Ziana; Meyrizka Salsabila (JURNAL TEKNIK HIDRAULIK, 2026)
The Syiah Kuala primary drainage channel in the Lhok Banie drainage block is located in Langsa Barat sub-district, Langsa City. This channel often experiences flooding due to the incapability of existing drainage channel to convey and accommodate stormwater discharge. One of the efforts to mitigate flood inundation is by conducting flood inundation modeling. This research aims to evaluate drainage channel capacity through water level profile modeling as well as to analyze the use of retention ponds as inundation flood control solution. Calculation of flood discharge is carried out using a modified rational method for subsequent use in modeling. Water level profile modeling using the HEC-RAS application was performed on a 2419 m long primary drainage channel and the retention pond analysis was conducted by considering the inflow and outflow discharge in the retention pond. The results of water level profile modeling with HEC-RAS show that the flood discharge elevation is above the elevation of the drainage channel cross-section. This means that the drainage channel capacity will no longer be able to accommodate the flood discharge for a 5-year return period. The channel experiences overtopping throughout its cross-section with maximum overtopping height of 1.23 m located in the channel downstream. The results of calculations for the retention pond using a pump with a capacity of 0.2 m3/s generate a retention pond volume of 32,678.92 m3. This retention pond was planned as flood storage area to temporarily store flood discharge in the Lhok Banie drainage block which has the potential to inundate the city, so that flood risk can be controlled.